Ende der Malerei und Malerei nach dem Ende der Malerei. - Meinhardt, Johannes (Ostfildern-Ruit : Cantz Verlag Ostfildern-Ruit, 1997)
Andre, Carl ; Baj, Enrico ; Bladen, Ronald ; Boehm, Gottfried ; Broodthaers, Marcel ; Buren, Daniel ; Cage, John ; Clert, Iris ; Dubuffet, Jean ; Duchamp, Marcel ; Fautrier, Jean ; Riverhead (New York) ; Fontana, Lucio ; Hegel, Georg W. F. ; Imdahl, Max ; Jermilow, Wassily ; Judd, Donald ; Kandinsky, Wassily ; Kant, Immanuel ; Kelly, Ellsworth ; Klein, Yves ; Krauss, Rosalind E. ; Lebenstein, Jean-Claude ; LeWitt, Sol ; Lissitzky, El ; Malevich, Kasimir ; Manzoni, Piero ; Marden, Brice ; Markow, Wladimir ; Matisse, Henri ; McCracken, John ; Mondriaan, Piet ; Morellet, François ; Newman, Barnett ; Palermo, Blinky ; Paolini, Giulio ; Péri, László ; Picabia, Francis ; Picasso, Pablo ; Polke, Sigmar ; Pollock, Jackson ; Puni, Iwan ; Rauschenberg, Robert ; Reinhardt, Ad ; Richter, Gerhard ; Rodchenko, Alexander ; Rothko, Mark ; Schulz-Hoffmann, Carla ; Schwitters, Kurt ; Steiner, Michael ; Stella, Frank ; Stepanowa, Warwara ; Strzeminski, Wladyslaw ; Tarabukin, Nikolai ; Tatlin, Wladimir ; Turowski, Andrzej ; Twombly, Cy ; Weidemann, Hinrich
Duits
boek